Análise microbiológica e físico-química de material proteico comestível derivado do processamento da gordura oriunda do abate de bovinos - Pereira, Juliano Goncalves [UNESP]; Soares, Vanessa Mendonca [UNESP]; Izidoro, Thiago Braga [UNESP]; Bersot, Luciano dos Santos; Almeida Nogueira Pinto, Jose Paes de [UNESP]; Biondi, Germano Francisco [UNESP] (Univ Fed Rio Grande do Sul, 2013)
Background: The use of all by-products of bovine slaughter is of high economic importance for the industries of products of animal origin. Among these products, fat has an important role, once fat rendering may generate several different products, such as protein material that may be used in the manufacture of meat products. However, in spite of the importance that the use of all by-products has for the economic balance of the industry, there are no reports on their use in Brazil, or studies that supply data on microbiological and physical-chemical local standards for this protein. Thus, the objective of this study was to evaluate microbiological and physical-chemical characteristics of protein material obtained from fat rendering, as well as to provide support for companies to use fat rendering to generate protein material, adding value to industrialized meat products.Materials, Methods & Results: The experimental production of edible protein obtained of fat rendering was conducted in slaughterhouse with supervision of the Brazilian Ministry of Agriculture, Livestock and Food Supply. Protein material was obtained in a continuous, humid heat system at high temperatures. Fat scraps containing protein were ground and cooked at high temperature (85 degrees C), and placed in a three phase decanter centrifuge. After centrifugation, protein material was ground again and packed. Samples were collected from 15 batches of protein material, and the following microbiological analyses were carried out: counts of aerobic mesophilic and psychrotrophic microorganisms, coliforms at 35 degrees C, Escherichia coli, sulfite-reducing Clostridium, and Staphylococcus aureus, besides presence or absence of Salmonella and Listeria monocytogens. The following physical-chemical analyses were also carried out: protein, total lipid, moisture, ash, carbohydrate, and energy content. Mean counts of mesophiles, psychrotrophs, and coliforms at 35 degrees C were 4.17; 3.69 and 1.87 (log CFU/g), respectively. Levels of protein, total lipids, moisture, ashes and carbohydrates were 27.50; 7.83; 63.88%; 0.24%; and 0.55%, respectively, and energy content was 182.63 kcal/100g.Discussion: Results of microbiological analyses demonstrated that, although low, the final product showed to be contaminated. Contamination that occurred during the second grinding procedure may be an explanation for these bacterial counts. Also, the temperature used for fat fusion was not enough to eliminate thermoduric microorganisms. However, even with the presence of indicator microorganisms in the samples, none was contaminated by E. coli, sulfite-reducing Clostridium, S. aureus, Salmonella or L. monocytogenes. Physical-chemical analyses showed that the product had adequate nutritional quality. Based on these results, it was possible to conclude that protein material obtained in fat rendering showed characteristics that enable the use of this product as raw material for processed meat products. Besides, the present study was the first one to present scientific results in relation to edible by-products obtained in fat rendering, supplying important information for slaughterhouses and meat-processing plants. The study also produced relevant data on the innocuousness of the product, which may be used to guide decision-making of health inspectors.
Microbiological and Physical-Chemical Analysis of Edible Protein Obtained as a By-Product of Fat Rendering in Cattle Slaughter
Keywords: bovine; by-products; fat; protein material; rendering; slaughter